Associations between the risk of LUTS/BPH and the number and class of chronic diseases among middle-aged and elder men - Hu, Zhigang; Tian, Yufeng; Hu, Xiaoqiao (Scientific reports, 2025)
We explored the associations between the risk of lower urinary tract symptoms suggestive of benign prostatic hyperplasia(LUTS/BPH) and the number and class of chronic diseases via cross-sectional and longitudinal studies.This study included 5197 men aged ≥ 45 years from the China Health and Retirement Longitudinal Study(CHARLS) 2011 with a 7-year follow-up. We multidimensionally investigated the relationships between LUTS/BPH and multimorbidity via latent class analysis, generalized additive analysis and causal mediation analysis. Latent class analysis identified four morbidity classes as follows: minimal or least common diseases (class 1, N = 4160, reference), dominant chronic lung diseases(class 2, N = 152), multiple chronic diseases(class 3, N = 387), and dominant heart diseases or risks(class 4, N = 498). In both the cross-sectional and cohort studies, the risk of LUTS/BPH increased in a dose-dependent manner with the number of chronic diseases. All multivariable-adjusted analyses suggested that three other classes had significantly greater risks of LUTS/BPH than did class 1. In the cross-sectional study, the risk of LUTS/BPH increased by 3.19 times(95%CI: 2.41 to 4.21) in class 3 than in class 1. Causal mediation analyses revealed that depression significantly mediated the association between LUTS/BPH and multimorbidity. Our results suggest that both the number and class of chronic diseases significantly affect the risk of LUTS/BPH.